Sharia Compliance of Ijarah Contracts in Umrah Plus Entertainment Packages: Formula One (F1) Phenomenon - Kayla Meidina Fadyasari; Muthoifin (proceedings.icesy, 2026)
In recent years, the development of religious tourism has influenced the practice of Umrah, particularly through the emergence of Umrah plus packages that combine ritual worship with additional services, including entertainment activities such as Formula One (F1) events. This study examines the contractual practice of Umrah services incorporating entertainment elements and analyze the Shari compliance of ijarah contracts applied in multiservice arrangements. The study focuses on how contractual structures regulate the integration of worship and entertainment within Umrah packages. A qualitative normative juridical approach is employed by examining Islamic legal principles, fatwas issues by the National Sharia Council of the Indonesian Ulama Council (DSN-MUI), and relevant academic literature on ijarah and religious tourism. The findings indicate that umrah services incorporating Formula One (F1) may remain permissible under Islamic law when the essential requirements of ijarah are fulfilled, particularly clarity of service objects, transparency of payment, and avoidance of gharar. This study further shows that entertainment activities may be accommodated as supplementary services as long as Umrah rituals remain the primary objective of the journey.